DIGITAL VISUAL BARK AN IMAGE BASED TOOL FOR PLANT DIVERSITY RESEARCH, DIVERSITY IN BARK SUPPORTS IN TREE IDENTIFICATION: Life Science-Botany - B. KALBANDE, RANJAN (International Journal of Life Science and Pharma Research, 2014)
Tree bark is protective and valuable. Tree bark was source of organic matter. The tree bark was traditionally used for medicinal purposes. In this present study, bark morphology of 40 trees belonging to compartment number 1016 research plot was studied. The tree bark was broadly classified on the basis of morphological characters, colour and texture whether it was smooth, scaly, furrowed, warty or shaggy. It was concluded that the diverse natures of the barks of the forest trees support for identification of species. It was found that out of 40 bark samples 16 were smooth, 5 scaly, 8 furrowed, 9 warty and 2 Shaggy types. From this study it was evident that the diverse natures of the barks the forest trees pave way for identification of species. There is an enormous amount of research being conducted in the medical field to determine the benefits of bark. In the present study, researcher tudied bark features and to prepare Digital Bark Library. Bark diversity of some species supports in tree identification.